Pelatihan Perakitan Komputer dan Instalasi Perangkat Lunak di Pondok Pesantren Darul Fithrah - Fitriani, Sofy; Setiarini, Siti Dwi; Sofyan, Yusuf (Universitas Nusantara PGRI Kediri, 2025)
Increasing students' capacity to increase students' competitiveness in the industrial world is one of the important things. Darul Fithrah Islamic Boarding School (Ponpes) is an Islamic educational institution aiming to provide religious education, formal education, and character development to its students. To realize this, the theme of community service was proposed as it was related to assembly training and computer installation. This training begins with the process of determining specifications and making training modules. The training process was attended by representatives of students, who immediately practised this computer assembly to understand the whole process. Then, students were delegated to train other students in computer assembly. Based on the results of the training, the students have understood the basics of computer components, computer assembly steps, how to install the operating system, how to install drivers, how to install computer software in general, and basic troubleshooting if there are problems around computers. The Ponpes also wanted the sustainability of cooperation related to further training because it was considered to have many benefits both in terms of institution and in terms of capacity building for the students.